Molecular detection and phylogenetic analysis of Kenyan human bocavirus isolates - Dennis Misigo; Dufton Mwaengo; David Mburu (Journal of Infection in Developing Countries)
Introduction: The commonly expected causative agents associated with flu-like symptoms in Kenya are the classical viral pathogens identifiable as influenza virus, adenovirus, parainfluenza virus, enteroviruses, respiratory syncytial virus (RSV) and rhinovirus. However, newer agents have been identified globally that present with illnesses clinically indistinguishable from those caused by the classical pathogens; one of them is human bocavirus. Methodology: A total of 384 specimens were analyzed, primarily to determine if the emerging human bocavirus (HBoV) infections exist in Kenya as coinfections with other respiratory viruses and to describe the genotype of the virus in circulation. In brief, viral nucleic acids were extracted from culture supernatants, amplified by PCR, and sequenced. Results: HBoV DNA was amplified from 1.8% of screened specimens. Coinfection with parainfluenza virus, adenovirus, and enterovirus was 2.5%, 2%, and 1.4%, respectively. Multiple coinfections consisting of HBoV plus two other viruses were found in 3% of specimens. Isolation occurred in the months of January, March, April, August, and November. Retrospective review of clinical parameters indicated that all the individuals complained of non-specific symptoms, mainly fever, coughs, nasal stuffiness, runny noses, and vomiting. Phylogenetically, the GenBank deposited sequences of this study’s isolates cluster closely to the reference strain NC_07455 (HBoV1). Conclusion: Coinfections with human bocavirus (HBoV1) occur in Kenya, and high incidence might primarily be during the early stages of children’s lives.